Impact of balloon aortic valvuloplasty on transcatheter aortic valve implantation with self-expandable valve. Issue 1 (January 2017) - Vavuranakis, Manolis; Lavda, Maria; Vrachatis, Dimitrios; Papaioannou, Theodore G.; Kalogeras, Konstantinos; Kolokathis, Angelos-Michail; Kariori, Maria; Lilly, Scott; Siasos, Gerasimos; Oikonomou, Evangelos; Toutouzas, Konstantinos; Stasinopoulou, Myrsini; et al.
Abstract: Background: Balloon aortic valvuloplasty (BAV) has been used prior to valve implantation of a self-expandable valve as part of the transcatheter aortic valve implantation (TAVI) procedure. We aimed to evaluate the impact of BAV prior to TAVI. Methods: We retrospectively studied 203 consecutive patients who were treated either with (pre-BAV-TAVI group) or without BAV (D-TAVI group). Implantation depth (ID) was angiographically measured at non-coronary cusp (NCC) and left coronary cusp (LCC) at: the starting point (stage-1), before (stage-2), and after (stage-3) final bioprosthesis release. Paravalvular regurgitation (PVR) and 1-year clinical follow-up were recorded. Results: Overall, from stage-1 to stage-3, prosthesis migrated toward the left ventricle, in both cusps and groups. At NCC a forward migration was observed from stage-1 to stage-2 in both groups ( p  < 0.001). In the pre-BAV-TAVI group only, at NCC, an upward migration decreased the ID from stage-2 to stage-3 ( p  = 0.022). PVR ≥grade 2, immediately after expansion was more frequently observed in pre-BAV-TAVI group (41% vs 22%, respectively; p  = 0.024). However, PVR was similar at discharge. Clinical parameters were comparable between the two groups. Conclusions: The use of BAV prior to TAVI may have an impact on device final position, but not on short- and long-term clinical outcome.